1998
DOI: 10.1002/(sici)1096-8652(199809)59:1<46::aid-ajh9>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin mutant, factor V Leiden, and thermolabile variant of methylenetetrahidrofolate reductase among patients with sickle cell disease in Brazil

Abstract: The prevalence of the prothrombin gene variant (allele 20.210 A), factor V Leiden mutation, and homozygosity for transition 677C-->T in the methylenetetrahydrofolate reductase (MTHFR) gene was determined among patients with sickle cell disease (SCD). The group included 73 patients with median age of 32.3 years with a diagnosis of sickle cell anemia in 53 patients, hemoglobinopathy SC in 16 patients, and four with S/beta(0) thalassemia. Vascular complications such as ischemic stroke or deep vein thrombosis were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 38 publications
3
54
2
2
Order By: Relevance
“…Inherited risk factors for vascular disease include factor V (FV) Leiden (G1691A/R506Q) [2], prothrombin (PRT) G20210A [3], and methylenetetrahydrofolate reductase (MTHFR) C677T point mutations [4]. In view of their role in enhancing thrombus formation, it was suggested that these mutations play a role in the pathogenesis of SCD [5,6] and/or its complications. In this study, the prevalence of these three point mutations was assessed in 87 SCD patients and 105 healthy controls from Eastern Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Inherited risk factors for vascular disease include factor V (FV) Leiden (G1691A/R506Q) [2], prothrombin (PRT) G20210A [3], and methylenetetrahydrofolate reductase (MTHFR) C677T point mutations [4]. In view of their role in enhancing thrombus formation, it was suggested that these mutations play a role in the pathogenesis of SCD [5,6] and/or its complications. In this study, the prevalence of these three point mutations was assessed in 87 SCD patients and 105 healthy controls from Eastern Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in general Brazilian population the mutant allele frequency ranged between 0.7%-3.6% (rs1799963*A) 23,24,25 . Brazilian population has an extremely heterogeneous ethnic composition, unevenly distributed across the country with variable degrees of admixtures 25 .…”
Section: Discussionmentioning
confidence: 98%
“…The sequences of the primers and the PCR conditions were previously described [10]. The product was digested with HinfI and the two fragments (175 and 23 bp, respectively) were demonstrated by gel electrophoresis as previously described [12,13].…”
Section: Methodsmentioning
confidence: 99%
“…A C→T substitution at nucleotide 677 in the methylenetetrahydrofolate reductase (MTHFR) gene is associated with a thermolabile phenotype and diminished enzyme activity with consequent hyperhomocysteinemia. Studies among SCD patients from Brazil [12] and the United States [13,14] have not demonstrated an association with ischemic stroke; however, Kutlar et al [15] identified this MTHFR mutation as a risk factor in the development of avascular Contract grant sponsor: Kuwait Research Grant; Contract grant number: MK034. necrosis (AVN) among their patients.…”
Section: Introductionmentioning
confidence: 99%